2004
DOI: 10.1002/clc.4960270510
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐specific association between preproendothelin‐1 genotype and reduction of systolic blood pressure during antihypertensive treatment‐‐‐results from the Swedish irbesartan left ventricular hypertrophy investigation versus atenolol (SILVHIA)

Abstract: SummaryBackground: Studies suggest that endothelin-1 contributes to the pathogenesis of hypertension. A G5665T gene polymorphism of preproendothelin-1 has been shown to be associated with higher blood pressure in overweight patients. No study has yet determined the effect of this polymorphism on the change in blood pressure during antihypertensive treatment.Hypothesis: This study aimed to determine this effect in hypertensive patients with left ventricular (LV) hypertrophy during antihypertensive treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…An A insertion into position 138 in the 5´UTR of the ET-1 gene has been associated with increased diastolic blood pressure [26]. The presence of the T allele in G5665T (198Lys/Asn) in exon 5 of the ET-1 gene was associated with elevated blood pressure, particularly in patients with a high body mass index [27][28][29] as well as an enhanced response to antihypertensive therapy in men [30]. Recently, the presence of the T allele in C1222T (1 kb downstream of the stop codon in the 3´UTR) in the ETRA gene was shown to correlate with decreased baroreflex sensitivity in normotensive and hypertensive individuals [31], whereas the presence of the AA allele in position 2013(+289)A/G in intron 17 of the ECE-1 gene was associated with increased basal blood pressure [32].…”
Section: Et-1 In Experimental and Human Hypertensionmentioning
confidence: 98%
“…An A insertion into position 138 in the 5´UTR of the ET-1 gene has been associated with increased diastolic blood pressure [26]. The presence of the T allele in G5665T (198Lys/Asn) in exon 5 of the ET-1 gene was associated with elevated blood pressure, particularly in patients with a high body mass index [27][28][29] as well as an enhanced response to antihypertensive therapy in men [30]. Recently, the presence of the T allele in C1222T (1 kb downstream of the stop codon in the 3´UTR) in the ETRA gene was shown to correlate with decreased baroreflex sensitivity in normotensive and hypertensive individuals [31], whereas the presence of the AA allele in position 2013(+289)A/G in intron 17 of the ECE-1 gene was associated with increased basal blood pressure [32].…”
Section: Et-1 In Experimental and Human Hypertensionmentioning
confidence: 98%
“…Cythochrome P450 polymorphisms in different dog breeds could have potential implications for Irb pharmacokinetics in clinical studies and a wider variety in the general dog population might be expected. Additionally, the fact that the present findings are generated by a small sample size with only male subjects should also be taken into consideration as, in humans, gender differences (Hallberg et al 2004, Lam et al 2012) in drug metabolism (Borobia et al 2009) have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…As it was found in the atenolol arm of the trial, the association between the preproendothelin-1 genotype and the BP reduction after therapy was gender-dependent [38].…”
Section: At1 Receptor Antagonistsmentioning
confidence: 90%
“…In patients treated with atenolol, two AGT polymorphisms predicted the BP decline after therapy [36]. The same was true for the preproendothelin-1 genotype, but only in males [38]. With regard to the SILVHIA trial it must be emphasized that the results were based on a very small cohort, which limits its usefulness.…”
Section: Beta-blockersmentioning
confidence: 96%
See 1 more Smart Citation